2005
DOI: 10.1080/10790268.2005.11753841
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Surgical Decompression in the Setting of Complete Thoracic Spinal Cord Injury

Abstract: Background/Objective: An assessment of neurological improvement after surgical intervention in the setting of traumatic thoracic spinal cord injury (SCI).Methods: A retrospective evaluation of a nonconsecutive cohort of patients with a thoracic SCI from T2 to T11. The analysis included a total of 12 eligible patients. The neurologic and functional outcomes were recorded from the acute hospital admission to the most recent follow-up. Data included patient age, level of injury, neurologic examination according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 53 publications
(48 reference statements)
0
24
0
Order By: Relevance
“…Second, there are small chances of SCI cure in the first 6-12 months. 4 Implications for prevention This study showed a high burden of 0.7 per 1000 population for SCI in Tehran in 2008. These results can be applicable for the urban population of 48 682 474 in Iran, which represents a multicultural collection of people from all over the country.…”
Section: Limitationsmentioning
confidence: 88%
See 2 more Smart Citations
“…Second, there are small chances of SCI cure in the first 6-12 months. 4 Implications for prevention This study showed a high burden of 0.7 per 1000 population for SCI in Tehran in 2008. These results can be applicable for the urban population of 48 682 474 in Iran, which represents a multicultural collection of people from all over the country.…”
Section: Limitationsmentioning
confidence: 88%
“…1 Injuries caused 28% of the total DALYs in Iran, and accounted for 60. 4 DALYs lost per 1000 of the population in Iran. 3 Fifty-three percent of the total numbers of DALYs in Iran were in male patients, and 47% of DALYs were in female patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, very little is known and reported about the prevalence of SCI in Iran (4)(5)(6)(7). This is the first published population-based study from Iran to estimate the prevalence of SCI in Tehran, Iran's capital.…”
Section: Introductionmentioning
confidence: 99%
“…5 The majority of outcome studies on patients with spine injuries focus mainly on the success of operative stabilization, clearance of the spinal canal or rapidity of the performed operation. 8,9 However, experimental and clinical studies have suggested that acute SCI is a two-step process involving primary and secondary mechanisms. Primary injury of the spinal cord refers to the initial mechanical damage by direct compression due to bone fragments or soft tissue causing damage of neural elements and blood vessels.…”
Section: Introductionmentioning
confidence: 99%